AGE induced macrophage-derived exosomes induce endothelial dysfunction in diabetes via miR-22-5p/FOXP1 - Yang Ji; Huanzhen Chen; Lihua Pang; Changnong Chen; Sha Wang; Jing Chen; Lei Fang; Benrong Liu; Yongruo Cheng; Shiming Liu; Yun Zhong (Cardiovascular Diabetology)
Abstract Background Endothelial dysfunction is a pivotal contributor to cardiovascular complications in individuals with diabetes. However, the precise role of macrophages and their exosomes in the diabetic milieu remains elusive. Methods Exosomes (Exos) were isolated from the supernatants of macrophages treated with advanced glycation end products (AGE) or bovine serum albumin (BSA) using ultracentrifugation. Following coculture with AGE-Exos or BSA-Exos, human umbilical vein endothelial cells (HUVECs) were subjected to CCK-8, EdU, cell migration, monocyte adhesion, and tube formation assays. ELISA and Western blotting were employed to assess inflammatory cytokine release and protein expression levels in HUVECs. The miRNA expression profiles of AGE-Exos and BSA-Exos were analysed using miRNA arrays. Potential targets of miR-22-5p were predicted via miRNA databases and validated through RT‒qPCR, dual-luciferase reporter assays, and rescue experiments. Furthermore, a Rab27a knockout mouse model of type 2 diabetes mellitus (T2DM) was established by intraperitoneal injection of Streptozotocin. Aortic tissues were analysed via immunofluorescence for CD63 and CD31 expression, immunohistochemistry for VCAM-1 and ICAM-1 expression, and Western blotting for FOXP1 expression. Results AGE stimulation increased the secretion of exosomes from macrophages. Compared with BSA-Exos, AGE-Exos significantly impaired endothelial cell proliferation, migration, and tube formation capabilities while increasing monocyte adhesion and proinflammatory cytokine release without affecting cell viability. miR-22-5p was enriched in AGE-Exos, which were subsequently transferred to HUVECs, specifically targeting FOXP1, resulting in endothelial dysfunction. Overexpression of miR-22-5p in HUVECs using lentiviral vectors recapitulated the inflammatory effects observed with AGE-Exos, whereas anti-miR-22-5p conferred protective effects. Rab27a knockout significantly reduced exosome accumulation in T2DM model mouse aortic tissues, alleviating endothelial discontinuity, downregulating VCAM-1 and ICAM-1 expression, and upregulating FOXP1 expression. Conclusions AGE-induced release of macrophage-derived exosomes may partially depend on Rab27a transport, which delivers miR-22-5p to ECs. This miR-22-5p targets FOXP1 in ECs, leading to inflammation and resulting in endothelial dysfunction that accelerates the development of diabetic vascular lesions.